Clinical Application of CT-Guided Percutaneous Microwave Ablation for the Treatment of Lung Metastasis from Colorectal Cancer - Lin Li; Ketong Wu; Haiyang Lai; Bo Zhang (Gastroenterology Research and Practice)
Objective. The aim of our research is to explore the clinical efficacy and safety of CT-guided percutaneous microwave ablation (MWA) for the treatment of lung metastasis from colorectal cancer. Materials and Methods. CT-guided percutaneous MWA was performed in 22 patients (male 14, female 8, mean age: 56.05 ± 12.32 years) with a total of 36 lung metastatic lesions from colorectal cancer between February 2014 and May 2017. Clinical data were retrospectively analyzed with respect to the efficacy, safety, and outcome. Results. Of the 36 lesions, 34 lesions (94.4%) reduced obviously with small cavitations or fibrous stripes formed and had no evidence of recurrence during follow-up. The volume of the other 2 lesions demonstrated local progression after 6 months by follow-up CT. The primary complications included pneumothorax (28%), chest pain (21%), and fever (5%). These symptoms and signs were obviously relieved or disappeared after several-day conservative treatment. The mean follow-up of the patients was 25.54 ± 12.58 months (range 2–41 months). The estimated progression-free survival rate was 94.4%. Conclusion. Our results demonstrate that CT-guided percutaneous MWA appears to be an effective, reliable, and minimally invasive method for the treatment of lung metastasis from colorectal cancer. This trial is registered with ChiCTR-ORC-17012904.